Integrating Brand Religiosity Image, E-Service Quality, and Muslim Customer Perceived Value: A Study on Muslim Student Loyalty Mediated by Satisfaction - Dede Ibrahim; Munirul Abidin; Indah Aminatuz Zuhriyah (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This study aims to analyze the effect of Brand Religiosity Image, E-Service Quality, and Muslim Customer Perceived Value on student loyalty, with student satisfaction as a mediating variable. This study was conducted at UIN Syarif Hidayatullah Jakarta using explanatory quantitative method. Data was collected through Google Form with a sample of 403 respondents from a population of 35,069 students. Data analysis was conducted using SmartPLS version 4.0.9.6. The results showed that Brand Religiosity Image, E-Service Quality, and Muslim Customer Perceived Value have a positive and significant influence on student loyalty. E-Service Quality and Muslim Customer Perceived Value also have a positive and significant effect on student satisfaction, but Brand Religiosity Image has no significant effect on student satisfaction. Student satisfaction has a positive and significant effect on student loyalty, but does not mediate the effect of Brand Religiosity Image on loyalty. Conversely, student satisfaction mediates the effect of E-Service Quality and Muslim Customer Perceived Value on student loyalty. These findings offer a new paradigm, namely the Islamic Higher Education Brand Religiosity Image (i-HEBRI), which emphasizes that Islamic universities need to internalize Islamic values and science in their brand and operations, and provide capable digital services to build student loyalty. This paradigm shows that to achieve student loyalty, it is not enough for institutions to have a strong brand image, but they also need to provide significant added value through quality services.